Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.coelec.2017.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-conducting polymer nanocomposites for enhancing electrochemical capacitive energy storage

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 92 publications
(56 reference statements)
0
16
0
Order By: Relevance
“…relatively low cycle stability), which results from their low intrinsic electrical conductivity and inadequate amount of electroactive sites. The proposed strategies to overcome the abovementioned problems include designed synthesis of nanostructures, binder-free electrodes grown on conductive substrates [84][85][86][87] and fabrication of nanohybrids with good conductive supports such as porous carbons [88][89][90][91], graphene [92][93][94][95] and conducting polymers [96][97][98][99][100][101]. It is well known that the electrochemical performances largely depend on the morphology and surface area of electrode materials; thus, the controlled synthesis of nickel sulfide nanomaterials with stable structure and large surface area is of great importance [102][103][104][105].…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…relatively low cycle stability), which results from their low intrinsic electrical conductivity and inadequate amount of electroactive sites. The proposed strategies to overcome the abovementioned problems include designed synthesis of nanostructures, binder-free electrodes grown on conductive substrates [84][85][86][87] and fabrication of nanohybrids with good conductive supports such as porous carbons [88][89][90][91], graphene [92][93][94][95] and conducting polymers [96][97][98][99][100][101]. It is well known that the electrochemical performances largely depend on the morphology and surface area of electrode materials; thus, the controlled synthesis of nickel sulfide nanomaterials with stable structure and large surface area is of great importance [102][103][104][105].…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…Liu et al reported tunable sulfuration engineered electrodes made from NiO/Ni 3 S 2 nanosheets constructed over a porous Ni foam and achieved a specific capacitance of 2153 F/g [ 112 ]. They constructed an asymmetric SC device using the NiO/Ni 3 S 2 nanosheets as the positive electrode, activated carbon as the negative electrode, and 3 M KOH as the electrolyte, and the device performance was evaluated by cyclic voltammetry (CV) study [ 109 , 110 , 111 ]. Liu et al considered that the redox reactions were the main reason for the good performance, and the CV features of their testing results are shown in Figure 5 .…”
Section: Advanced Electrodes For Scs: Present Status and Prospectsmentioning
confidence: 99%
“…Another challenge for graphene to be used in electronic applications lies in the π-π stacking interactions of the graphitic sheets, which tends to result in their self-aggregation [108]. To counter this aggregation challenge, the distribution of metal/metal oxide over the graphitic sheets could be a useful strategy, which could also increase the surface area and conductivity of the graphitic sheets [109]. Among various metal oxides, NiO has been widely investigated for SC applications.…”
Section: Metal-based Electrodesmentioning
confidence: 99%
“…As shown in Table 2, current SCs are classified as i) double layer SCs (using the charge-storing ability of the electrical double layer (EDL) formed on the electrode/ electrolyte interface), ii) pseudo-SCs (employing so-called pseudocapacitive surface or near-surface charge transfer reactions), and iii) hybrid SCs combining electrodes of first two types, which are capable to provide high energy density, close to that of conventional Li-ion batteries. [89] In recent decades, significant improvements in capacitance and operational stability, and faster and cheaper synthesis methods of nanocomposite materials have been reported. These include activated carbon, nanotubes, and graphene.…”
Section: Supercapacitorsmentioning
confidence: 99%
“…These include activated carbon, nanotubes, and graphene . The pseudocapacitive features of various conducting polymers, transition metal oxides, and sulfides have also been widely used in pseudo‐ and hybrid SCs …”
Section: Supercapacitorsmentioning
confidence: 99%